2016
DOI: 10.1021/acs.langmuir.6b00531
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Aminopropyltriethoxysilane-Polydopamine Coatings

Abstract: Polydopamine coatings are of interest due to the fact that they can promote adhesion to a broad range of materials and can enable a variety of applications. However, the polydopamine-substrate interaction is often noncovalent. To broaden the potential applications of polydopamine, we show the incorporation of 3-aminopropyltriethoxysilane (APTES), a traditional coupling agent capable of covalent bonding to a broad range of organic and inorganic surfaces, into polydopamine coatings. High energy X-ray photoelectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 71 publications
1
45
0
Order By: Relevance
“…A coating thickness of ~1 μm was possible to achieve by this method by varying dopamine:PEI ratio and reaction time. Similarly, Knorr et al reported the use of APTES as organic base for the preparation of pDA-silicate composite films in both neutral and basic pH conditions [30]. In both pH, the coating thickness and coating speed depend on APTES:dopamine ratio.…”
Section: Accelerating the Coating Speed Of Pda Coatingsmentioning
confidence: 96%
“…A coating thickness of ~1 μm was possible to achieve by this method by varying dopamine:PEI ratio and reaction time. Similarly, Knorr et al reported the use of APTES as organic base for the preparation of pDA-silicate composite films in both neutral and basic pH conditions [30]. In both pH, the coating thickness and coating speed depend on APTES:dopamine ratio.…”
Section: Accelerating the Coating Speed Of Pda Coatingsmentioning
confidence: 96%
“…In this article, we will focus on polydopamine (PDA), an apparent dark, insoluble material as a functional thin film material for biosensor and biomedical applications. PDA is in particular interesting because (i) it can be synthesized by alkali‐induced autoxidation of dopamine; (ii) it shows excellent adhesive properties on almost every type of materials such as metals, semi‐conductors, polymers, or even nanoparticles; (iii) it exhibits excellent biocompatibility because of the similarity to melanin (eumelanin) occurred in nature; (iv) it can be incorporated with other functional groups (e.g., SH or NH 2 ) because chemical structures such as catechol, amine, or imine are available . Due to this multifold potential of PDA, a great number of investigations have been carried out to study the influence of experimental parameters on the film structural and growth/polymerization mechanisms of PDA particles and thin films in the past few years.…”
Section: Introductionmentioning
confidence: 99%
“…The mussel adhesive-inspired polydopamine (PD) appears to be an ideal biomaterial coating since it fulfils all these criteria. It exhibits low cytotoxicity [2], antibacterial properties [3,4], promotes cell growth [5][6][7][8], resists corrosion [9], can aid antibiotic release [10,11], is simple to produce with control over film thickness [12] and can be attached to a variety of surfaces including silanes [13], metals [9,14], polymers [7,[15][16][17] dentine [18] and even hair [19].…”
Section: Introductionmentioning
confidence: 99%